2015
DOI: 10.1159/000376586
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dyadic Matching of Affect on Infant Self-Regulation

Abstract: Background/Aims: Affective behavioural matching during face-to-face interaction fosters the transition from mutual regulation to infant self-regulation. Optimum midrange models of mother-infant interaction hold that moderate degrees of dyadic matching facilitate infant socio-emotional development. The aim of this study was to examine which degree of dyadic matching is most beneficial for infant self-regulation. Methods: To evaluate this model, 3 groups of highly, midrange and poorly matched dyads were created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Previous research on risk factors for infant development found a negative impact of maternal depression [17,18] and anxiety [19,20] and has focused on maternal sensitivity [21,22] and mother-infant interaction [23,24]. Recently, Dalsant et al [25] demonstrated that parental bonding moderated later stress response to social stimuli in the adult offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on risk factors for infant development found a negative impact of maternal depression [17,18] and anxiety [19,20] and has focused on maternal sensitivity [21,22] and mother-infant interaction [23,24]. Recently, Dalsant et al [25] demonstrated that parental bonding moderated later stress response to social stimuli in the adult offspring.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of this implicit knowledge of relationship might be of vital importance for infant emotional development. Recently, matching states were demonstrated to be associated to infant affective regulation [14]. Nevertheless, to our knowledge, there are no studies using micro-analytic and psychobiological measurements, which evaluate the hypothesis that short latencies to the reparation of micro-temporal affective mismatching states scaffold infant regulation whereas long latencies increase dysregulation and distress [15].…”
Section: Introductionmentioning
confidence: 99%
“…The category "Limitations in Care" refers to the caregiver's actions toward the child regarding their protection, interaction, and affectionate relationships. In this category, the exposure factors were: Difficulties in interacting with the child, 13,[15][16]18,20,27,32,35,38,53,55,67,[75][76]81,86,90,93,96,101,116,119 Difficulties in meeting the socioemotional needs of the child, 61,79,91,99 Low duration of breastfeeding, 81 Attitude of overprotection towards children, 26 Anxiety of parents facing difficulties of the child, 112 Absence of caregiver affection towards the child, 118 Negative perception of children, 47,59 Absence of reading and learning moments with the child, 19,108 Excessive control and regulation of parents due to cultural influence, [110][111] Authoritative posture towards the child, 47,117 Presence of violence and abuse against children, 47,60,68,83,113 Absence of protection against accidents…”
Section: /21mentioning
confidence: 99%
“…[27][28]56,65,77 The category "Caregivers 'illness situation" refers to health-disease conditions that may impair the caregivers' ability to bond and provide affective relationships. In this category, the exposure factors were: presence of depression and stress of caregivers, 14,33,36,38,56,60,67,73,[75][76][78][79]94,98 schizophrenia and other mental disorders of caregivers, 39,68,89,97 anxiety of caregivers, 59 compulsive disorders in caregivers, 40 depression and pre and postnatal stress, 12,18,28,30,43,46,48,[51][52]57,[64][65]68,70,85,100,103 nutritional impairment during prenatal care 38 and caregivers' chemical dependence. 15,18,36,60,…”
Section: /21mentioning
confidence: 99%